Megachile sculpturalis, the Giant Resin Bee, overcomes the blossom structure of Sunn Hemp (Crotalaria juncea) that impedes pollination - Hall, H Glenn; Avila, Laura (Journal of Melittology, 2016)
Bee species that are effective pollinators of sunn hemp (Crotalaria juncea L.: Fabaceae: Crotalarieae) are few in number because of the large size and papilionaceous structure of the plant’s blossom. Seed for this potentially valuable cover crop is largely unavailable due to the paucity of pollinators and to the plant’s self-incompatibility. The introduced Megachile (Callomegachile) sculpturalis Smith (Megachilidae: Megachilinae), the giant resin bee, has the anatomy and behavior to be a most effective pollinator. While holding onto the upper vexillum petal of the blossom with her mandibles, this bee has the strength to depress the lower keel causing pollen to be expelled by the style through the small opening at the end. The bee is long enough for its metasoma to extend over the end of the keel, and, as a member of the family Megachilidae, has scopal hairs on the venter of the metasoma, which are thus in an optimal position to contact the pollen. Honey bees (Apis mellifera L.: Apidae) are common visitors to sunn hemp flowers but are too small to be effective pollinators. A honey bee worker robs the pollen by inserting her proboscis into the end of the keel and extracting the adhering pollen. Possible problems could result from mutual enhancement of populations of an exotic bee and an exotic plant.